1999
DOI: 10.1074/jbc.274.9.5333
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte-Macrophage Colony-stimulating Factor-activated Signaling Pathways in Human Neutrophils

Abstract: Granulocyte-macrophage colony-stimulating factor (GM-CSF) regulates many of the biological activities of human neutrophils. The signaling pathways via which these effects are mediated are not fully understood. We have shown previously that GM-CSF treatment of human neutrophils activates the Janus kinase/signal transducers and activators of transcription (Jak/STAT) pathway and, more specifically, Jak2, STAT3, and STAT5B in neutrophils. GM-CSF also stimulates the activity of the phosphatidylinositol 3-kinase (PI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(31 citation statements)
references
References 72 publications
3
28
0
Order By: Relevance
“…Several other reports provided further evidence for coordinated activation of PI3-K and Stat proteins leading to the functional cooperation of both signaling cascades (47,48). Moreover, recent studies demonstrated the ability of Jaks to associate with and to regulate the p85 subunit of PI3-K, as was shown for Jak3 in human T cells (49), Jak1 in cardiac myocytes (50), and Jak2 in human neutrophils (51).…”
Section: Discussionmentioning
confidence: 65%
“…Several other reports provided further evidence for coordinated activation of PI3-K and Stat proteins leading to the functional cooperation of both signaling cascades (47,48). Moreover, recent studies demonstrated the ability of Jaks to associate with and to regulate the p85 subunit of PI3-K, as was shown for Jak3 in human T cells (49), Jak1 in cardiac myocytes (50), and Jak2 in human neutrophils (51).…”
Section: Discussionmentioning
confidence: 65%
“…Each member has a conserved C-terminal kinase domain. Jak2 was reported to activate PI-3K␣, but the exact mechanism by which these two molecules interact is unclear (50). This Jak2-dependent PI-3K␣ pathway is unlikely to signal LPC-induced eNOS promoter function, because transfection of ⌬p85, which blocks PI-3K␣ activity, had no effect of eNOS promoter activity.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that GM-CSFinduced neutrophil survival requires Src-kinase-mediated activation of PI3K [26]. Others have found the involvement of JAK2 in GM-CSF-mediated granulocyte survival [27][28][29].…”
Section: Pi3k Signalling and Granulocyte Apoptosismentioning
confidence: 99%